ChemInform Abstract: 3‐Fluorotetrahydropyran‐4‐one Derivatives from Homopropargyl Acetal. Issue 39 (23rd September 2014) - Aaseng, Jon Erik; Iqbal, Naseem; Sperger, Christian A.; Fiksdahl, Anne
Abstract Title compound (V) is synthesized from homopropargyl acetal (III) via Petasis—Ferrier rearrangement/cyclization and subsequent regioselective 3‐fluoro incorporation.